El recaudo de impuestos tributarios en el municipio de Neiva vigencia 2016 – 2020 dado el covid19. - Palomo, Catalina (Universidad Antonio Nariño, 2021)
The research proposal presents an analysis of the projected budget and the collection of tax revenues corresponding to the period from 2016 to 2020 of the Municipality of Neiva, on the other hand, the impact of the collection on the budget of expenses is studied, especially in the axes strategic plans contemplated in the municipality's development plan.